2014
DOI: 10.1038/ncomms6378
|View full text |Cite
|
Sign up to set email alerts
|

Highly accelerated inverse electron-demand cycloaddition of electron-deficient azides with aliphatic cyclooctynes

Abstract: Strain-promoted azide-alkyne cycloaddition (SPAAC) as a conjugation tool has found broad application in material sciences, chemical biology and even in vivo use. However, despite tremendous effort, SPAAC remains fairly slow (0.2-0.5 M À 1 s À 1 ) and efforts to increase reaction rates by tailoring of cyclooctyne structure have suffered from a poor trade-off between cyclooctyne reactivity and stability. We here wish to report tremendous acceleration of strain-promoted cycloaddition of an aliphatic cyclooctyne (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
146
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 159 publications
(163 citation statements)
references
References 44 publications
5
146
0
3
Order By: Relevance
“…Even more markedly, picryl azide was found to react with norbornene almost 1000 times faster than phenyl azide [2]. Based on these observations, we recently concluded that the apparent slower reaction of electron-poor azides in SPAAC only holds for benzoannulated cyclooctynes (with low-lying LUMO), while in combination with more electronrich cyclooctynes (like BCN), azides can react by a second, inverse electrondemand mechanism (i.e., SPAAC) as well [20]. As a result, it was first found that strain-promoted cycloaddition of aromatic azides with BCN is nearly eight times faster than with DIBAC, which is the opposite trend for reaction with benzyl azide.…”
Section: Influence Of Azide Structure On Reaction Ratementioning
confidence: 98%
“…Even more markedly, picryl azide was found to react with norbornene almost 1000 times faster than phenyl azide [2]. Based on these observations, we recently concluded that the apparent slower reaction of electron-poor azides in SPAAC only holds for benzoannulated cyclooctynes (with low-lying LUMO), while in combination with more electronrich cyclooctynes (like BCN), azides can react by a second, inverse electrondemand mechanism (i.e., SPAAC) as well [20]. As a result, it was first found that strain-promoted cycloaddition of aromatic azides with BCN is nearly eight times faster than with DIBAC, which is the opposite trend for reaction with benzyl azide.…”
Section: Influence Of Azide Structure On Reaction Ratementioning
confidence: 98%
“…In a combined experimental and theoretical investigation with the van Delft group, we showed that the rate of fast SPAAC reactions between electron‐poor azides (Ar‐N 3 ) and bicyclononyne (BCN) is dictated by an inverse electron demand (IED) FMO interaction (see Scheme 1). 33 …”
Section: Applications In Chemistrymentioning
confidence: 99%
“…10 Although we were able to achieve diazo group-specific conjugation in the absence of a catalyst (Scheme 1), the reaction rates were low—comparable to those obtained with early SPAAC reagents and exceeded by new SPAAC reagents. 8c,11 Hence, we sought a faster cycloaddition.…”
Section: Introductionmentioning
confidence: 99%